2017
DOI: 10.1007/978-3-319-66653-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Gut-Bone Signaling

Abstract: The intestinal environment is linked to an array of conditions and diseases, including osteoporosis. Human and animal studies indicate that probiotics can benefit intestinal health and may provide a useful therapeutic to prevent and/or treat bone loss. Probiotics are defined as live microorganisms that when administered in adequate amounts will confer a health benefit on the host. In this review, we will focus on 1) probiotics (definition, history, nomenclature, types), 2) the effects of probiotics on bone hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 103 publications
(191 reference statements)
3
36
0
Order By: Relevance
“…(121) In addition to altering the gut microbiome and reducing intestinal inflammation, probiotics are known to promote intestinal barrier function and benefit bone health. (50,(53)(54)(55)(56)(57)63,67,68,71,73,75,76,(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132) Consistent with these studies, we found that treatment with LR as well as LGG uniquely altered the microbiota composition, which was significantly different from mice treated with GC alone. We hypothesize that each of these compositions have a different balance of healthy versus disease-promoting bacteria, which could be playing a role in its differential effects on the intestinal barrier and furthermore bone health.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…(121) In addition to altering the gut microbiome and reducing intestinal inflammation, probiotics are known to promote intestinal barrier function and benefit bone health. (50,(53)(54)(55)(56)(57)63,67,68,71,73,75,76,(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132) Consistent with these studies, we found that treatment with LR as well as LGG uniquely altered the microbiota composition, which was significantly different from mice treated with GC alone. We hypothesize that each of these compositions have a different balance of healthy versus disease-promoting bacteria, which could be playing a role in its differential effects on the intestinal barrier and furthermore bone health.…”
Section: Discussionsupporting
confidence: 85%
“…The Lactobacilli strains LGG and LR are both used as probiotics to benefit the health of mice and humans. (126) Both LR (L. reuteri 6475) and LGG are human-derived strains that do not (in the case of L. reuteri) or are not expected to (in the case of LGG) colonize the mouse gut. Because we did not disrupt the microbiome prior to addition of the probiotics, it is unlikely that the probiotics colonized the gut.…”
Section: Discussionmentioning
confidence: 99%
“…antibiotic overuse, exposure to pollution and poor nutritional intake), has led to a ‘dysbiotic drift’ (Logan, 2015). Indeed, dysbiosis or ‘life in distress’ is considered by some researchers to manifest as an imbalance in the microbial assemblages in the human body to a state that is detrimental to health (Logan, Jacka, & Prescott, 2016; Schepper et al, 2017; Sokol et al, 2019). However, it is important to note that the complexities of characterizing ‘dysbiotic’ patterns are considerable and the concept remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Since valeric acid is produced by probiotic bacteria 15 , we calculated the Spearman correlation between B.vulgatus and common probiotic bacteria 16,17 Table 6). MR-Egger (intercept) result (p-value = 0.517) showed no horizontal pleiotropy for B.vulgatus to influence valeric acid levels.…”
Section: Scfas Significantly Associated With Bmdmentioning
confidence: 99%
“…https://doi.org/10.1101/2020.03. 16 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Gene Expression In Osteoclast-like Cells and Osteoblastsmentioning
confidence: 99%